Positive impact of adding No.14v lymph node to D2 dissection on survival for distal gastric cancer patients after surgery with curative intent - Liang, Yuexiang; Wu, Liangliang; Wang, Xiaona; Ding, Xuewei; Liu, Hongmin; Li, Bin; Wang, Baogui; Pan, Yuan; Zhang, Rupeng; Liu, Ning; Liang, Han (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Background: D2 lymphadenectomy has been increasingly regarded as standard surgical procedure for advanced gastric cancer (GC), while the necessity of No.14v lymph node (14v) dissection for distal GC is still controversial. Methods: A total of 920 distal GC patients receiving at least a D2 lymph node dissection in Department of Gastric Cancer, Tianjin Medical University Cancer Institute and Hospital were enrolled in this study, of whom, 243 patients also had the 14v dissected. Other 677 patients without 14v dissection were used for comparison. Results: Forty-five (18.5%) patients had 14v metastasis. There was no significant difference in 3-year overall survival (OS) rate between patients with and without 14v dissection. Following stratified analysis, in TNM stages I, II, IIIa and IV, 14v dissection did not affect 3-year OS; in contrast, patients with 14v dissection had a significant higher 3-year OS than those without in TNM stages IIIb and IIIc. In multivariate analysis, 14v dissection was found to be an independent prognostic factor for GC patients with TNM stage IIIb/IIIc disease [hazard ratio (HR), 1.568; 95% confidence interval (CI): 1.186-2.072; P=0.002]. GC patients with 14v dissection had a significant lower locoregional, especially lymph node, recurrence rate than those without 14v dissection (11.7% vs. 21.1%, P=0.035). Conclusions: Adding 14v to D2 lymphadenectomy may be associated with improved 3-year OS for distal GC staged TNM IIIb/IIIc.